Health Care Reform: Where Do We Go From Here? - Dukakis, Michael (Maine Policy Review, 1994)
Will universal health insurance ever become a reality? In this, based on his address in October as the 1994 Margaret Chase Smith Lecturer, former Massachusetts Governor Michael S. Dukakis suggests that efforts to establish universal coverage will continue. He argues, however, that the success of these efforts depends on the public adhering to the principle that all citizens will contribute to a system of universal coverage.